The Influence of Light Rare-Earth Substitution on Electronic and Magnetic Properties of CoFe2O4 Nanoparticles - Rareș Bortnic; Adam Szatmari; Tiberiu Dragoiu; Radu George Hategan; Roman Atanasov; Lucian Barbu-Tudoran; Coriolan Tiusan; Raluca Lucacel-Ciceo; Roxana Dudric; Romulus Tetean (Nanomaterials)
Co0.95R0.05Fe2O4 nanoparticles with R = La, Pr, Nd, Sm, and Eu were synthesized via an environmentally friendly sol–gel method. The prepared samples were studied using X-ray diffraction measurements (XRD), transmission electron microscopy (TEM), X-ray photoelectron microscopy (XPS), and magnetic measurements. All compounds were found to be single phases adopting a cubic Fd-3m structure. EDS analysis confirmed the presence of Co, Fe, R, and oxygen in all cases. The XPS measurements reveal that the Co 2p core-level spectra are characteristic for Co3+ ions, as indicated by the 2p3/2 and 2p1/2 binding energies and spin–orbit splitting values. The analysis of the Fe 2p core-level spectra reveals the presence of both Fe3+ and Fe2+ ions in the investigated samples. The doped samples exhibit lower saturation magnetizations than the pristine sample. Very good agreement with the saturation magnetization values was obtained if we assumed that the light rare-earth ions occupy octahedral sites and their magnetic moments align parallel to those of the 3d transition metal ions. The ZFC-FC curves indicate that some nanoparticles remain superparamagnetic, while others exhibit ferrimagnetic ordering at room temperature, suggesting the presence of interparticle interactions. The Mr/Ms ratio at room temperature reflects the dominance of magnetostatic interactions.